Stochastic Modeling of Solar Flare Duration at Pakistan Atmospheric Region - Saifuddin Ahmed Jilani; M. Ayub Khan Yousuf Zai; Afaq Ahmed Siddiqui (Journal of Basic & Applied Sciences, 2015)
Energy incident from the Sun is the chief deriving force responsible for all physical process existing in our terrestrial system. It is interesting to note that solar ultraviolet (UV) radiation created ozone in our stratosphere by the dissociation of O2 molecules. On the other hand, the streams of solar particle flux deplete ozone by creating NOx in our atmosphere. It is therefore, an important task to quantify the contribution of solar activity on OLD with the scientific assurance. In this communication the stochastic models of solar flare duration as solar activity have been investigated. Digisonde, at SUPARCO, HQ one of the ground based device provide us the record of solar flare duration by investigating the ionosphere disturbance. The behavior of solar activity have accomplished by the stochastic modeling in addition to their residual analysis. Since there are two major kinds of flares, it is necessary to establish what the different parametric configurations that causes their difference and their behavior in solar terrestrial relationship. Evidences suggest that gradual flares may become serious threat for our atmospheric and terrestrial disturbances. Their frequency most closely related with high activity periods. However sometimes this could be accomplished in low activity period as well. Hence, it is quite relevant to study theoretical and observational aspects of both high and low activity periods. The data recorded from March 1979 to March 2006 was consisting of mixed flares.